In vitro and in vivo assessment of polyherbal topical gel formulation for the treatment of acne vulgaris - Pratibha Nand; Sushma Drabu; Rajinder K. Gupta; Aseem Bhatnagar; Rashid Ali (International Journal of Drug Delivery, 2012)
Anti-acne herbal formulations are used for the treatment of acne vulgaris with the added advantage of not producing adverse effects unlike synthetic drugs. Phytoconstituents present in methanolic extracts of Camellia sinensis (CSME), Glycyrrhiza glabra (GGME) and Calendula officinalis (COME) have antibacterial and antioxidant properties. Validated HPTLC fingerprinting confirmed the presence of myricetin (CSME), glycyrrhizin (GGME) and kaempferol (COME) in these extracts. Extracts loaded with carbopol® 940 were used for the preparation of herbal (F1-F3) and polyherbal gel (PHF), followed by evaluation for pH, viscosity, spreadability and in vitro antibacterial potential against S. aureus, S. epidermidis and P.acnes. Polyherbal gel formulation indicated antibacterial potential and was further assessed for skin permeation by gamma scintigraphy using hydrophilic radiotracer 99mTc-DTPA and lipophilic radiotracer 99mTc-MIBI. Significant permeation (78.11%) was observed with hydrophilic radiotracer labeled 99mTc-DTPA-PHF and this suggested that the formulation was capable of sustained drug delivery for the treatment of moderate to severe type of acne.